2014
DOI: 10.3934/jgm.2014.6.261
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbits in the Kepler-Heisenberg problem

Abstract: The Kepler-Heisenberg problem is that of determining the motion of a planet around a sun in the Heisenberg group, thought of as a three-dimensional sub-Riemannian manifold. The sub-Riemannian Hamiltonian provides the kinetic energy, and the gravitational potential is given by the fundamental solution to the sub-Laplacian. The dynamics are at least partially integrable, possessing two first integrals as well as a dilational momentum which is conserved by orbits with zero energy. The system is known to admit clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Periodic orbits. The existence of periodic orbits was established in [11]. However, the proof followed the direct method in the calculus of variations and provided very little information about such orbits beyond their existence.…”
Section: Resultsmentioning
confidence: 99%
“…Periodic orbits. The existence of periodic orbits was established in [11]. However, the proof followed the direct method in the calculus of variations and provided very little information about such orbits beyond their existence.…”
Section: Resultsmentioning
confidence: 99%
“…where κ is a non-zero real parameter. The properties of this system have been analysed in [9,12], where it was shown that is has an invariant submanifold given by z = 0, p z = 0, p θ = xp y − yp x = 0 on which all trajectories are straight lines. More importantly, it was also demonstrated that all periodic solutions must lie on the zeroenergy level and that the whole system is Liouville integrable there.…”
Section: Introductionmentioning
confidence: 99%
“…where κ is a non-zero real parameter. The properties of this system have been analysed in [4,9,12], where it was shown that it has an invariant submanifold given by z = 0, p z = 0, p θ = xp y − yp x = 0 on which all trajectories are straight lines. More importantly, it was also demonstrated that all periodic solutions must lie on the zero-energy level and that the whole system is Liouville integrable there.…”
Section: Introductionmentioning
confidence: 99%